Exploring the Core Attributes of Digitalization Causing High Impact on Learning Trends Of Students Using LIFAM - Martin, Nivetha; Pandiammal, P (International Journal of Engineering and Technology, 2018)
In the existing educational scenario, the mechanisms of teaching and learning that are conventional have to be enriched unanimously to promote the development of the student community in all dimensions. The present government rings the bell of Digital India, which targets in making the service sectors to be digitally empowered. But in recent days, digitalization has stepped into almost all the fields and education is not an exception to it. The traditional blackboard teaching method was replaced by ICT techniques, but the learning strategies remained customary. To bring a change in the learning mode, the student community has to be provided a platform to learn at their own pace, which can be achieved by imparting the digital way of learning. Incorporation of Digitalization into teaching cum learning domains will pave way for Glean knowledge. Though there are many confrontations in implementation, the degree of the positive effects is high. This paper primarily aims in determining the effects of core factors of digitalization causing major effects on studentâ€™s learning mode using a novel approach of Linguistic Induced Fuzzy Associative Memories (LIFAM).Â Â
Keywords: Associative memories; Digitalization; Fuzzy; learning trends; Linguistic variable